2018
DOI: 10.3389/fnmol.2018.00219
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Alterations in the Trigeminal Ganglia, Nucleus and Peripheral Blood Mononuclear Cells in a Rat Orofacial Pain Model

Abstract: Orofacial pain and headache disorders are among the most debilitating pain conditions. While the pathophysiological basis of these disorders may be diverse, it is generally accepted that a common mechanism behind the arising pain is the sensitization of extra- and intracranial trigeminal primary afferents. In the present study we investigated gene expression changes in the trigeminal ganglia (TRG), trigeminal nucleus caudalis (TNC) and peripheral blood mononuclear cells (PBMC) evoked by Complete Freund's Adjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 91 publications
6
34
1
1
Order By: Relevance
“…El manejo de las cefaleas experimentó una evidente mejoría con la creación en 1988 de la Clasificación Internacional del Dolor de cabeza (International Headache Classification), con la cual, no solo el diagnóstico, sino también el conocimiento de las frecuencias de los distintos tipos de dolor en la sociedad y sus respectivos tratamientos han evolucionado ampliamente (97). Aunque la base fisiopatológica de los diferentes tipos de cefaleas puede ser muy diversa, en todos ellos existe una sensibilización de las aferencias del nervio trigémino (a nivel intra o extracraneal) (98).…”
Section: Cefaleasunclassified
“…El manejo de las cefaleas experimentó una evidente mejoría con la creación en 1988 de la Clasificación Internacional del Dolor de cabeza (International Headache Classification), con la cual, no solo el diagnóstico, sino también el conocimiento de las frecuencias de los distintos tipos de dolor en la sociedad y sus respectivos tratamientos han evolucionado ampliamente (97). Aunque la base fisiopatológica de los diferentes tipos de cefaleas puede ser muy diversa, en todos ellos existe una sensibilización de las aferencias del nervio trigémino (a nivel intra o extracraneal) (98).…”
Section: Cefaleasunclassified
“…The pathomechanism of these disorders may be further investigated by using animal models with the activation of nociceptive pathways of the TS [1,3,5]. The administration of inflammation-inducing substances to the orofacial area can evoke the above-described activation/sensitization of the primary and secondary trigeminal neurons during pain processing [6,7]. For the induction of this peripheral inflammation, the application of Complete Freund's adjuvant (CFA) into the whisker pad or the dural parietal surface is a widely used method [6,8,9] as it is able to enhance local reaction at the injection site and then to evoke the release of inflammatory cytokines, alongside with hyperalgesia/allodynia on the face via the activation/sensitization of the TS [7].…”
Section: Introductionmentioning
confidence: 99%
“…The administration of inflammation-inducing substances to the orofacial area can evoke the above-described activation/sensitization of the primary and secondary trigeminal neurons during pain processing [6,7]. For the induction of this peripheral inflammation, the application of Complete Freund's adjuvant (CFA) into the whisker pad or the dural parietal surface is a widely used method [6,8,9] as it is able to enhance local reaction at the injection site and then to evoke the release of inflammatory cytokines, alongside with hyperalgesia/allodynia on the face via the activation/sensitization of the TS [7]. Regarding the delay of the development of peripheral and central sensitization, indirect data from studies with CFA injection to the paw demonstrated that pain hypersensitivities were observed 24 h after the injection [9][10][11][12][13], whereas data from studies with orofacial CFA model, more precisely from the temporomandibular joint induced inflammation model, suggest that both thermal and mechanical allodynia peak at 24 h as well [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathomechanism of these disorders may be further investigated by using animal models with the activation of nociceptive pathways of the TS [1,3,5]. The administration of inflammation-inducing substances to the orofacial area can evoke the above-described activation/sensitization of the primary and secondary trigeminal neurons during pain processing [6,7]. For the induction of this peripheral inflammation, the application of Complete Freund's adjuvant (CFA) into the whisker pad or the dural parietal surface is a widely used method [6,8,9] as it is able to enhance local reaction at the injection site and then to evoke the release of inflammatory cytokines, alongside with hyperalgesia/allodynia on the face via the activation/sensitization of the TS [7].…”
Section: Introductionmentioning
confidence: 99%